Introducing Silverlight 4 - Ghoda, Ashish. (Apress : Imprint: Apress, 2010)
Introducing Silverlight 4 brings you up to speed with version 4 of Silverlight quickly and efficiently. The book builds off your understanding of the basics of .NET coding and WPF, allowing your journey to Silverlight 4 proficiency to be as quick and painless as possible. The text highlights where coding techniques are similar to other, more established areas of the .NET framework. Likewise, when your existing coding habits lead you to a syntax or conceptual ’gotcha,’ the text points that out, too. This book provides you with fast-track coverage of all the most important elements of the Silverlight 4 technology ranging from XAML to standard controls, from dealing with media to networking, from testing to deployment. It also reveals features introduced with Silverlight 4 and offers guidance on how to best utilize them. The book concludes with a pair of fully worked sample applications for you to follow through, because nothing reinforces your understanding of how concepts fit together as much as looking at finished code. It is assumed that readers are already be comfortable with the workings of the .NET framework. Knowledge of Expression Blend is useful, but not mandatory: you’ll learn the Blend techniques that you need to know as you go through the book. By the end, you will have followed a sound, concise path to mastery of Silverlight 4.